Pengaruh Kompleksitas Tugas dan Locus Of Control Terhadap Hubungan Antara Gaya Kepemimpinan dan Kepuasan Kerja Auditor - Cecilia Engko; Gudono Gudono (Jurnal Akuntansi dan Auditing Indonesia, 2007)
This research examined the effect of task complexity and locus of control to relationship between leadership style and job satisfaction. This research applies leadership style with contingency approach and Path Goal Theory of Leadership. The sampling technique is purposive sampling. Data collected by sending questionnaire direct to various public accountant offices (KAP). The respondents are junior auditors in Surabaya, Semarang and Yogyakarta. The junior auditors partici¬pated in this research are 90 respondents of 19 Public accountant Offices (KAP).Hypothesis testing is using Two Way Analysis of Variance (ANOVA). The result of this research indicates that the lower task complexity; supportive leadership style will increase job satisfaction of junior auditors. This research also shows that task complexity could not moderate the relation between directive leadership style and job satisfaction, locus of control could not moderate the relation between directive leadership style and job satisfaction, locus of control could not moderate relation between supportive leadership style and job satisfaction.Keyword:    Direct leadership style, supportive leadership style, task complexity, locus of control and job satisfaction.